Identification of Mangrove Zonation in Sondaken Village, Bunaken National Park Area - Michellia Pamela Sanggor; Mercy Maggy Franky Rampengan; Helen Joan Lawalata; Anita Costanci Christine Tengker; Rievo Handry Djarang (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
Sondaken Village has three mangrove zones, each with its own type of plant. The first zone, facing directly towards the sea, is dominated by Avicennia sp. The second zone, in the middle, is characterized by Rizophora sp. The third zone, closer to the land, is predominantly Bruguiera sp. Mangroves have different levels of growth, including seedling level, stake level, pole level, and tree level. The purpose of this study was to determine the types and growth levels of mangroves within its zonation in Sondaken Village, which is part of Bunaken National Park Area. This was done using exploratory and descriptive survey methods, by creating 3 plots in each zone from the edge to the center, with sizes of 10x10 m2, 5x5 m2, and 2x2 m2. The research found that mangrove in Sondaken Village consist of Avicennia sp, Rizophora sp, and Bruguiera sp, with the number of individuals per species being 124, 133, and 113 individuals respectively. Each type of mangrove has different growth levels and numbers.